Artificial Intelligence and Global Security: Strengthening International Cooperation and Diplomatic Relations - Titilayo Modupe Kolade (Archives of Current Research International, 2024)
This study investigates how artificial intelligence (AI) can enhance global security by fostering international cooperation and diplomatic relations. It examines the dual nature of AI, where operational benefits such as improved cybersecurity, military precision, and threat detection are offset by significant ethical and geopolitical challenges. Through a mixed-methods approach, the research identifies key issues like geopolitical tensions and fragmented governance while highlighting the opportunities for collaboration through multilateral research and ethical AI governance. The findings reveal notable improvements in AI-driven cybersecurity, with detection rates increasing from 86% in 2021 to 88.25% in 2023 and mitigation rates rising from 80.75% to 83.75%. However, AI-driven attacks also increased from 11.25 incidents in 2021 to 16.25 in 2023, underscoring the risks associated with AI misuse. The study emphasizes the importance of robust governance frameworks that promote transparency, accountability, and ethical AI use across borders. It concludes that international cooperation, supported by ethical AI governance, is crucial to maximize AI’s potential in addressing global security challenges, with specific recommendations for enhancing existing frameworks such as the OECD AI Principles and the Global Partnership on AI.